Ernest Becker's Dark Turn (1971-1973): A Critical "Deepening". (March 2019) - Martin, Jack; Liechty, Daniel
The "dark turn" evident in Ernest Becker's final two major works ( The Denial of Death and Escape From Evil ) is described and explained in terms of its content and possible sources in the author's work and life from 1971 to 1973. Becker's mature philosophical anthropology, anthropodicy, and theory of evil are discussed, related to, and contrasted with his previous work and considered in the context of his life experiences, including his terminal illness.